Implementing Dynamic System Reconfiguration with Renewables Considering Future Grid Technologies: A Real Case Study - José Filipe Soares Pogeira (2018)
The electric power systems are in an evolutionary process to respond not only to environmental concerns, but also to integrate more distributed renewable energy sources (DRES), the increase of demand and the integration of new technologies. The multiplicity integration of elements aims the creation of the future electricity grids, the Smart Grids. In this sense, it is necessary to create optimization techniques to improve the current electrical power system, being the distribution system one part of the electrical power system that needs to be optimized. Dynamic distribution system reconfiguration is the process of changing the network topology during the system operational periods. This process together with the integration of DRES and other technologies, namely energy storage systems, will allow a greater system optimization in technical and economic terms, but also a greater integration of DRES. In this optimization process the stochastic nature of DRES (its variability and uncertainty) are taken in consideration. In this dissertation, an improved dynamic system reconfiguration model is presented where the goal is to minimize the total costs of the system, namely costs of operation, maintenance, emissions and energy not supplied. The system optimization is made considering the various technical system constraints, operating the system in a reliable and stable way. The computational tool is tested in two test systems, the IEEE 119-bus system and in a real system, the system of Lagoa, (in São Miguel Island, Azores) to validate the effectiveness of the proposed method.